Paralel Taxiway Runway 16 untuk Optimalisasi Flow Traffic - Mulorrosrianti, Michelle; Rossydi, Ahmad; Akhyar, Rajul; Sugiyanto (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
This report was aimed to give advice to optimize flow traffic in Perum LPPNPI Branch Pangkalpinang by using parallel taxiway runway 16. This report used observation method that was implemented in Airnav Pangkalpinang for five more months. There were several cases that was written in this report to support the advice to optimize flow traffic in Perum LPPNPI Branch Pangkalpinang. Based on cases that was collected, the way to solve the cases by adding parallel taxiway runway 16 to optimize flow traffic.